Cryptocurrency analysis based on user-generated social media content - Narciso, Miguel de Guerra (2020)
Bitcoin is a cryptocurrency that has started to become interesting in 2017 as a result of the massive hype the cryptocurrency has created around the world, claiming to be the first fully digital coin based on blockchain technology. There are people reacting and commenting everyday about Bitcoin on social networks and online forums. The known social networks that drive significant opinions related with Bitcoin are Twitter and Reddit. It can be said that Bitcoin may attribute much of its growth to the Reddit social forum. This research is dedicated to the study of the application of Sentiment Analysis to the Reddit users’ comments on daily discussion publications from Bitcoin - Reddit community with the goal to find a correlation between these results and Bitcoin’s known indicators. The study aims to analyze the sentiment of the Bitcoin discussion threads, having two main research questions: 1. Do users’ comments of the daily discussion posts have a correlation with the daily indicators of Bitcoin? 2. Do users’ comments of the daily discussion posts have a correlation when the indicators information of Bitcoin are shifted by a few days? The research has permitted to analyze the correlations between the different indicators.